Manejo biotécnico do arroio Guarda-Mor: princípios, processos e práticas - Sutili, Fabrício Jaques (2004)
Slope instability and erosion of the soil by water are major environmental hazards. Although they are the result of natural geomorphological processes, they are both affected by and have consequences for human activity, often incurring economic and social damage. The use of vegetation for slope stabilization and erosion control can be referred to as soil bioengineering. In Europe (especially in Germany, Switzerland and Austria) and in the United States, pioneers have been using bioengineering for many decades. However, in Brazil, these techniques are still little known, given the lack of a systematic vision, observations and experiments that allow your diffusion and use. This work describes the erosion processes of the ‘Guarda-mor’ stream and aims to state the potential of using soil bioengineering and demonstrate the science (principles) and practices. As well, to describe and analyse the research base underlying soil bioengineering in order to provide a better understanding of the role of vegetation (native species) and how it can be regarded as an engineering material. Success was obtained with the two soil bioengineering’s techniques, constructed with local material, in an economical and practical way. Among the four studied species only Calliandra brevipes showed not to be promising as engineering material. Phyllanthus sellowianus, Salix humboldtiana and Sebastiania schottiana, are promising engineering material.